Tools and Guidelines for Sustainable Student Mobility - Baggia, Alenka; Brezavšček, Alenka; Pažur Aničić, Katarina; Tomičić Furjan, Martina; Lendelova, Lucie; Petrović, Nataša (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The increasing international mobility of students poses significant challenges to sustainability efforts due to the environmental impact of travel and daily activities. In response, universities and stakeholders are increasingly emphasizing environmentally friendly practices to reduce the carbon footprint of students studying abroad. This paper provides a comprehensive overview of the available tools, initiatives and guidelines to promote sustainable behaviours of students participating in international mobility programs. Through a structured review of available literature, guidance and case study analysis, this paper identifies existing resource gaps and highlights best practices for promoting environmentally sustainable behaviours. The findings highlight the need for a user-friendly benchmarking tool that integrates different dimensions of sustainability, including transportation, energy consumption, waste management and community engagement. This study contributes to the broader discourse on sustainable student mobility and is a foundation for developers of a useful tool to drive meaningful environmental change in higher education.